"The Agency of Refugees and Asylum-Seeking Women in the Face of the Inability of States to Provide Protection Against Sexual and Gender-Based Violence" - Sarkin, Jeremy Julian (2024)
Drawing on fieldwork in Greece, Uganda, and Israel, this empirical study is an enquiry into the forms of agency adopted by refugee and asylum-seeking women who are survivors of, or in situations of risk of, sexual and gender-based violence. The article identifies the main agentic behaviors reported by participants to prevent and address multiple and intersecting discriminations leading to sexual and gender-based violence. It ascertains various types of agency, including passive versus active agency; silence as agency versus silence as oppression; and individual versus collective agency. The study then also asks what functions these forms of agency fulfill. It finds that they are responses to the state’s failure to prevent and address sexual and gender-based violence in four ways: (1) to acknowledge asylum-seekers sufficiently; (2) to protect asylum-seekers from sexual and gender-based violence; (3) to guarantee access to justice to sexual and gender-based violence survivors; and finally (4) to prevent further discrimination of the hosted community. Thus, this article argues that refugees and asylum-seekers adopt different types of agency to react against the state’s inability to provide protection from sexual and gender-based violence.